STRATEGI PENINGKATAN KUALITAS PELAYANAN RAWAT INAP DI PUSKESMAS BULANG KECAMATAN BULANG - Khalida, Khalida; Dompak, Timbul; Sianturi, Sahat (SCIENTIA JOURNAL, 2019)
The purpose of this research is to describe a strategy to improve quality inpatient services at the Bulang Health Center Bulang District. This study uses descriptive research method with qualitative approach. This collection process is carried out by means of observation of interview and documentation. Interviews was conducted with Doctor, nurses, and patients in Bulang District. This research analyzed method analysis of Stranght, Weakness, Opportunity, Threat (SWOT) paying attention to internal and external factors. Based results the study using the SWOT analysis the strategies used by Bulang Community Health Center improve the quality of inpatient services are: (A) StrengthOpportunity SO Strategy namely Improving the quality inpatient services Improving the quality and supply of medicines available also improving work same between employees. (B) strength-threat, Increasing collaboration between the Bulang Health Center and the community. (C) Weakness-Oppportunity WO Strategy, which is to to make quality human resources in accordance their profession also repair facilities infrastructure to repair the quality of services at the Puskesmas. (D) Weakness-Threat WT Strategy, Improving, accordance with their fields order to provide good quality services to community Bulang District. Based on these results, hoped Bulang Health Center will improve the quality of services, especially in inpatient services.